Sending out an SOS? Evaluating transmission of Elsinoë australis from packinghouse treated Citrus fruit - Lindsey Danielle Thiessen; Evan Braswell; Ashton Leo; Dara Stockton; Annette Diaz; Mayra Reyes (Plant Health Progress, 2026)
Sweet orange scab, caused by Elsinoë australis, is a disease of regulatory concern. In the United States, sanitation treatments are required to ship fruit outside of quarantine zones to reduce the risk of spreading regulated pathogens affecting Citrus fruits to unaffected areas. Fruit with symptoms of sweet orange scab were collected from organic and conventional packinghouses in Texas, both before and after processing. Elsinoë australis was isolated onto semi-selective media from both conventional and organic processed fruit at equivalent rates for either processing practice and recovery of viable colony forming units collected from unprocessed fruit was significant compared to processed (P = 0.009). There was no significant difference between organic and conventional packinghouse procedures on detection using the regulatory molecular assay protocols for E. australis, but fruit treated with either organic or conventional postharvest packing procedures had significantly greater detection compared to non-treated fruit (P < 0.001). Collected fruit, both treated and nontreated, were used in splash dispersal experiments and disease was monitored on small trees. There were no significant differences between organic or conventional practices, and only non-treated, symptomatic fruit could transmit the disease with splash dispersal. The experiments described were designed to encourage disease, and it is unlikely that postharvest fruit would be subjected to those conditions. Both organic and conventional packinghouse procedures provided equivalent risk mitigation for fruit in areas affected by sweet orange scab.